(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
The cultivation of soursop (Annona muricata L.) is one of the most popular in Colombia, since its fruit is very consumed and requires good care for its marketing, in recent years has been increasing the area sown. The applying of chemicals products to these tres for the reduction of the disease that affects them, anthracnose (Colletotrichum gloeosporioides) is a constant; therefore, this project investigated other alternatives testing organic products prepared from plant extracts or biofertilizer that can reduce and control the incidence and severity of this disease, in order to replace agrochemicals that leave residuality and can be detrimental to human health. For these tests the following treatments were established: Mucuna pruriens (T1), Datura stramonium (T2) and a biofertilizer (T3) to compare the severity of the disease against a control (T0); was applied a completely random design, four treatments, three replicates with three experimental units, the evaluations were carried out at seven, twelve and eighteen days after the application of these products. The percentage of decrease with respect to the initial severity which was taken as zero (0), shows that the products that gave a positive result (P<0.05) in applications progressively against anthracnose disease were: the Mucuna pruriens plant extract and the biofertilizer being 78.35 vs 18.36 and 50.81 vs 20% respectively, comparing the initial severity with that presented at 18 days after the application of products. It is concluded that the best treatments were the Mucuna pruriens followed by biofertilizer.